Effects of Rhizobacteria Strains on Plant Growth Promotion in Tomatoes (Solanum lycopersicum) - Eduardo Hernández-Amador; David Tomás Montesdeoca-Flores; Néstor Abreu-Acosta; Juan Cristo Luis-Jorge (Plants)
Numerous factors, such as soil fertility, climatic conditions, human activity, pests, and diseases, limit agricultural yields. Pesticides and fertilizers have become indispensable tools to satisfy the global food demand. However, its adverse environmental effects have led to the search for more sustainable and ethical techniques. Biofertilizers and biopesticides based on plant- growth-promoting rhizobacteria (PGPRs) are efficient and ecological treatments that promote plant growth and protection against pathogens and abiotic stresses. In this study, twelve rhizobacterial strains with plant-growth-promoting attributes were selected to evaluate their plant-growth-promoting effect on tomato plants (Solanum lycopersicum L. var Robin). Soil inoculation with these strains resulted in a significant increase in shoot length, up to 50% when compared with control plants. Regarding fresh biomass, rhizobacterial treatments significantly improved seedlings’ fresh aerial weight with a maximum increase of 77%. Root biomass also demonstrated a substantial improvement, yielding 62.26% greater fresh root weight compared to the control. Finally, dry root weights exhibited the most remarkable enhancements, with values between 49 and 124%, when compared to the control plants. Concerning the nutritional status, the strains inoculation increased the macronutrients and micronutrients content in the aerial and root parts of the plants. All these findings suggest that rhizobacteria from different ecosystems and agriculture soils of the Canary Islands could be used as fertilizer inoculants to increase crop yield and promote more sustainable practices in modern agriculture.